Analisis Permintaan Air Bersih di Kota Bengkulu - Nugroho, Iwan; Nugroho, Yuni Agung; -, Zaenuddin - (Jurnal Manajemen Akuntansi dan Bisnis, 2008)
The research was aimed to study demand and willingness to pay of householdâs pipe water in Bengkulu. Survey was conducted on the household whose pipe and unpipe water connection. Analysis methods were pipe water demand and qualitative choice model. The research result showed that household conneting pipe water consumed on average amount of 19.9 m3 per month. Meanwhile, water demand was significantly affected by price (with elasticity ofâ1,95) and income of 0.103. Amount of 90 percentage of household unconnecting pipe water stated their well water under good quality. On the other side, 47 percent of household connecting peipe water stated the same condition. The willingnes to pay of pipe water connection positively related with telephone installed and size of land. While, income elasticity of the willingness to pay was found amount of 0.793. Keywords: pipe water, willingness to pay, and water demand